PENGARUH MOTIF, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Empiris Pada Konsumen Di Sinar Mas Seluler Cabang Plaza Simpang Lima Lantai Dasar Semarang ) - Try Sugiarto, 13.05.51.0191; Widyasari, Suzy (Students Journal of Economic and Management, 2018)
This purpose of this study was to analysis the effect of motif, product quality, and perceived price to purchasing decision of smartphone Samsung in Sinar Mas Cellular Plaza Simpang Lima The Ground Floor Semarang.The population in this study were consumers who made a purchase of smartphone Samsung at Sinar Mas Cellular Plaza Simpang Lima The Ground Floor Semarang. The number of samples studied were as many as 100 peoplewere selected as respondents used purposive sampling technique. Data collection methods used in this study was questionnaire filled out by respondents.The analysis used in this study was multiple linear regression to examine the effect of partially each independent variable,there were motivation, product quality and perceived price to dependent variable that was purchasing decesion. The results of this study showed that motivation, product quality, and perceived price had a positive and significant effect on purchasing decisions at Sinar Mas Cellular Plaza Simpang Lima The Ground Floor Semarang.Keyword: Motif, Product Quality, Perceived Price and Purchasing Decision Process